ta có x√8y−5≤√3x√8y−53≤√32x(8y−53+1)=√33x(4y−1) ⇒VT(1)≤√33(8xy−x−y)≤√33(2(x+y)2−x−y) VP ≥4√24(12((x+y)2+4))=4√12(x+y)2+96 ta cần cm 4√12(x+y)2+96≥√33(2(x+y)2−x−y) đặt t=x+y ⇔4√12t2+96≥√33(2t2−1) nâng lũy thừa bậc 4 ⇔(t−2)(t7+3t25+5t24+8t163+81t82+27t2+2)≤0 ⇔t≤2 ta cần tìm đk này từ pt (2) vs t-x=y (2) ⇔11x2−6x(t−x)+3(t−x)=12x−4(t−x) ⇔20x2−(16+12t)x+3t2+4=0 Δ′≥0⇔t∈[−43;2] ⇒x=y=1
ta có
x√8y−5≤√3x√8y−53≤√32x(8y−53+1)=√33x(4y−1) ⇒VT(1)≤√33(8xy−x−y)≤√33(2(x+y)2−x−y) VP
≥4√24(12((x+y)2+4))=4√12(x+y)2+96 ta cần cm
4√12(x+y)2+96≥√33(2(x+y)2−x−y) đặt
t=x+y ⇔4√12t2+96≥√33(2t2−1) nâng lũy thừa bậc 4
⇔(t−2)(t7+3t25+5t24+8t163+81t82+27t2+2)≤0 ⇔t≤2 ta cần tìm đk này từ pt (2) vs t-x=y (2) $\Leftrightarrow 11x^{2}-6x(t-x)+3(t-x)
^{2}=12x-4(t-x)
\Leftrightarrow 20x^{2}-(16+12t)x+3t^{2}+4
t=0
\Delta' \geq 0 \Leftrightarrow t\in \left[ \frac{-4}{3}{;}2 \right]
\Rightarrow x=y=1$